Penyuluhan Dampak Penggunaan Game Online kepada Siswa SMA Negeri 1 Buntu Pane - Zulfan Efendi; Tika Christy; Febby Madonna Yuma (Smart Education, 2021)
Abstract: The internet is one example of the results of current technological developments and advances, the internet provides many forgiveness and convenience for us, with the internet information is easier for us to get. Online games are one type of game that utilizes devices connected to the internet network as a medium. The existence of online games today, becomes a new challenge for students, this is because at this time is a period of child development. the development of learning motivation becomes a new challenge for teenagers and children as students as students. Various games that attract students so that it has an impact on their social activities and school achievement. Changes in behavior in adolescents who are addicted to mobile games may not be felt by the students themselves, but can be felt by others in their environment, especially parents and teachers. The purpose of this service is to increase the knowledge of SMA Negeri 1 Buntu Pane students regarding the impact of online game addiction behavior on adolescent health. The method used is interactive lectures and questions and answers about counseling the impact of addiction to playing online games. there is an increase in the knowledge of SMA Negeri 1 Buntu Pane students about the negative impact of online games on health.Keywords: Counseling; Game online; Health Abstrak: Internet merupakan salah satu contoh hasil dari perkembangan dan kemajuan teknologi saat ini, internet banyak memberikan maafaat dan kemudahan bagi kita, dengan internet informasi lebih mudah kita dapatkan. Game online adalah salah satu jenis permainan yang memanfaatkan perangkat yang terkoneksi jaringan internet sebagai medianya. Adanya game online saat ini, menjadi suatuÂ tantanganÂ baruÂ bagiÂ paraÂ pelajar,Â halÂ iniÂ dikarenakanÂ padaÂ masaÂ ini adalah masa perkembangan anak. pembangunan motivasi belajar menjadi suatu tantangan baru bagi remaja dan anak-anak selaku siswa-siswi sebagai peserta didik. BeragamÂ gameÂ yangÂ menarikÂ paraÂ siswaÂ sehinggaÂ berdampakÂ terhadap aktifitas pergaulannya dan prestasi sekolah mereka. Perubahan perilaku pada remaja yang mengalami kecanduan game mobileÂ mungkin tidak dirasakan oleh siswaÂ itu sendiri, tetapi dapat dirasakan oleh orang lain dilingkungan mereka khususnya orang tuaÂ dan guru. Tujuan pengabdian ini adalah untuk meningkatkan pengetahuan siswa SMA Negeri 1 Buntu Pane mengenai dampak perilaku kecanduan game online terhadap kesehatan remaja. MetodeÂ yangÂ digunakan adalah ceramah interaktif dan tanya jawab tentang penyuluhan dampak kecanduan bermain game online. adanya peningkatan pengetahuan siswa SMA Negeri 1 Buntu Pane tentangÂ dampakÂ negatifÂ gameÂ onlineÂ bagi kesehatan.Kata kunci: Game Online; Kesehatan; Penyuluhan